2019
DOI: 10.1186/s10033-019-0408-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cutting Parameters for Trade-off Among Carbon Emissions, Surface Roughness, and Processing Time

Abstract: As the manufacturing industry is facing increasingly serious environmental problems, because of which carbon tax policies are being implemented, choosing the optimum cutting parameters during the machining process is crucial for automobile panel dies in order to achieve synergistic minimization of the environment impact, product quality, and processing efficiency. This paper presents a processing task-based evaluation method to optimize the cutting parameters, considering the trade-off among carbon emissions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Arriaza et al [17] established a multi-objective response optimization method for processing time and processing energy consumption, and finally found that spindle speed is the main factor of energy consumption, and cutting width is the most important factor affecting processing efficiency. Jiang et al [18] proposes a cutting parameter optimization method based on an evaluation model of machining tasks, which also takes into account carbon emissions, surface roughness and machining time. Some researchers proposed a multi-objective optimization model to reduce energy consumption based on machining process planning, which takes into account processing efficiency and machine tool energy consumption [19][20][21][22], but they did not consider processing quality in the optimization modeling process.…”
Section: Cutting Parameters Optimization Methodsmentioning
confidence: 99%
“…Arriaza et al [17] established a multi-objective response optimization method for processing time and processing energy consumption, and finally found that spindle speed is the main factor of energy consumption, and cutting width is the most important factor affecting processing efficiency. Jiang et al [18] proposes a cutting parameter optimization method based on an evaluation model of machining tasks, which also takes into account carbon emissions, surface roughness and machining time. Some researchers proposed a multi-objective optimization model to reduce energy consumption based on machining process planning, which takes into account processing efficiency and machine tool energy consumption [19][20][21][22], but they did not consider processing quality in the optimization modeling process.…”
Section: Cutting Parameters Optimization Methodsmentioning
confidence: 99%
“…The signal-to-noise (S/N) ratio is particularly utilized in the Taguchi method to study the influence of each factor [37]. Because the uniformity, the typical of interest in this investigation, should be as close as possible to zero, a "smaller the better" formula is employed for the S/N ratio calculation as follows [39], [40]:…”
Section: 2mentioning
confidence: 99%
“…Previous research such as [6,7,8,9] stated that machining parameters such as cutting speed, feed rate, and depth of cut can affect the energy and costs incurred during machining. Arif, et al [10] developed an energy optimization model consisting of machining, idle, tool replacement, and cutting tool energy.…”
Section: Introductionmentioning
confidence: 99%